Cardiorespiratory and antinociceptive effects of two different doses of lidocaine administered to horses during a constant intravenous infusion of xylazine and ketamine - Nobrega Neto, Pedro I. (2013)
Background: This study investigated the antinociceptive effects of a constant rate infusion (CRI) of lidocaine during xylazine and ketamine anesthesia in horses and aimed to correlate these effects with cardiorespiratory variables, bispectral index (BIS) and plasma lidocaine concentrations. Six adult crossbred mares weighing 320-400 kg were anesthetized on three different occasions. Sedation was performed with xylazine (0.75 mg/kg IV) and anesthetic induction with guaifenesin (75 mg/kg IV) and ketamine (2 mg/kg IV). Anesthesia was maintained with 37.5 mu g/kg/min of xylazine and 87.5 mu g/kg/min of ketamine both administered intravenously for 75 min. The three treatments consisted of: lidocaine (loading dose: 5 mg/kg, CRI: 100 mu g/kg/min; THL); lidocaine (loading dose: 2.5 mg/kg; CRI: 50 mu g/kg/min: TLL); and saline (TS); all given 15 min after induction and maintained for 1 h. Antinociception was measured by response to electrical stimulation and bispectral index (BIS) was recorded during anesthesia. Parametric and non-parametric data were compared using ANOVA followed by Student-Newman-Keuls and Friedman tests, respectively.Results: Plasma lidocaine concentrations peaked at the end of lidocaine loading dose and was greater in THL (9.61 +/- 2.75 mu g/mL) vs TLL (4.50 +/- 3.34 mu g/mL). Electrical noxious stimulation caused purposeful movement in all horses from TS, but no response in THL. The BIS was decreased in THL only and was less when compared to the other treatments throughout anesthesia. Blood pressure, PaO2 and PaCO2 increased and heart rate (HR), respiratory rate (RR), pH, total plasma protein and temperature decreased during anesthesia in all treatments. PaCO2 and HR were greater and RR and pH less in THL compared to TLL and TS at 30 min during anesthesia. All recoveries were considered excellent. Time to standing was longer after THL (60 +/- 20 min) than following TLL and TS (32 +/- 17 and 30 +/- 15 min, respectively).Conclusions: At the highest dose administered (THL) lidocaine CRI during xylazine/ketamine anesthesia decreased BIS and motor response to noxious stimulation, and prolonged recovery time without significant added cardiorespiratory depression.